SOCIO-ECONOMIC APPROACHES TO THE STUDY OF THE STANDARD OF LIVING AND WELFARE OF THE POPULATION (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article analyzes the main socio-economic approaches used to measure the standard of living and well-being of the population. The role of indicators such as human capital, income, education and health in determining the standard of living is highlighted. It reveals how the development of human capital affects the economic development of countries. Also, analyses are presented on the example of the Republic of Uzbekistan based on indicators for measuring well-being, including the Human Development Index, Gini coefficient and Human Capital Indexes.
Keywords: standard of living, well-being, human capital, income inequality, Gini index, human development index, economic growth, education, health, socio-economic analysis.